The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1111/j.1600-0714.1973.tb01848.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of Danish snuff‐induced oral leukoplakias

Abstract: Abstract. In a sample of 450 patients with oral leukoplakias, 32 used snuff, which was a Danish wet variety, Göteborg snus ® (Gothenburg Snuff). The group of snuff users consisted of males only, with a mean age of 58.4 years. The mean life exposure time lo snuff was 197,000 hours, the equivalent of 22 years of constant use. Patients with leukoplakia due lo the use of snuff experienced fewer symptoms than did patients with leukoplakia due to other unknown causes. The snuff users also tended to be older at firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Studies on the histopathology of mucosal reaction have been carried out in the United States (Smith et al, 1970), Denmark (Roed-Peterson and Pindborg, 1973) and Sweden (Andersson et al, 1989;Axell et al, 1976) whereby epithelial changes have been described, but in most cases, such changes were seen in the outermost layers of the mucosa only. Axell et al (1976), in the material of 114 biopsies from current snuff dippers in Sweden, found no cellular atypia or epithelial dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the histopathology of mucosal reaction have been carried out in the United States (Smith et al, 1970), Denmark (Roed-Peterson and Pindborg, 1973) and Sweden (Andersson et al, 1989;Axell et al, 1976) whereby epithelial changes have been described, but in most cases, such changes were seen in the outermost layers of the mucosa only. Axell et al (1976), in the material of 114 biopsies from current snuff dippers in Sweden, found no cellular atypia or epithelial dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…According to several reports, the leukoplakias that harbor candidal hyphae appear to constitute from 7 to 50% of all leukoplakias (Jepsen and Winther, 1965;Roed-Petersen et al, 1970;Daftary et al, 1972;Roed-Petersen and Pindborg, 1973;Bánóczy, 1982;Krogh et al, 1987b). Lehner (1971) has suggested that differential counts of pyroninophilic monocytes be carried out to distinguish between candidal and non-candidal leukoplakias.…”
Section: (12) Epidemiological and Demographic Aspects Of Chc: Incidementioning
confidence: 99%
“…Dysplasia in smokeless tobacco keratosis is quiet rare accounts for less than 3% of cases; which is a condition that precedes and often indicates malignancy potentiality [6,[16][17][18]. A retrospective study in Sweden found only one case of malignant transformation, an extremely low frequency [19].…”
Section: Discussionmentioning
confidence: 99%